Volume 1: Turbomachinery 1995
DOI: 10.1115/95-gt-233
|View full text |Cite
|
Sign up to set email alerts
|

The Design and Performance of a High Work Research Turbine

Abstract: This paper describes the design and performance of a high work single stage research turbine with a pressure ratio of 5.0, a stage loading of 2.2 and cooled stator and rotor. Tests were carried out in a cold flow rig and as part of a gas generator facility. The performance of the turbine was assessed, through measurements of reaction, rotor exit conditions and efficiency, with and without airfoil cooling. The measured cooled efficiency in the cold rig was 79.9%, which, after correcting for temperature and meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Moustapha et al [7] (Highly Loaded Turbine) showed the effect of blade loading on high loaded ( H /U 2 = 2.4) stage efficiency at off-design conditions; increase in the rotor blade loading by 53 per cent reduced the efficiency by 2.5 per cent. Vlasic et al [8] (High Work Research Turbine) investigated a single-stage turbine with a pressure ratio of 5 and stage loading of 2.2, the efficiency is reduced by 2.1 per cent when the turbine-cooling rate goes from 0 to 11 per cent. Woinowsky-Krieger et al [9] showed that a 10 per cent reduction in the rotational speed resulted in a decrease of 3 per cent in the efficiency for a single-stage transonic turbine.…”
Section: Introductionmentioning
confidence: 98%
“…Moustapha et al [7] (Highly Loaded Turbine) showed the effect of blade loading on high loaded ( H /U 2 = 2.4) stage efficiency at off-design conditions; increase in the rotor blade loading by 53 per cent reduced the efficiency by 2.5 per cent. Vlasic et al [8] (High Work Research Turbine) investigated a single-stage turbine with a pressure ratio of 5 and stage loading of 2.2, the efficiency is reduced by 2.1 per cent when the turbine-cooling rate goes from 0 to 11 per cent. Woinowsky-Krieger et al [9] showed that a 10 per cent reduction in the rotational speed resulted in a decrease of 3 per cent in the efficiency for a single-stage transonic turbine.…”
Section: Introductionmentioning
confidence: 98%
“…Rich experience was accumulated through the investigation, however, the shape of the blade was all convergent ones and the loss level was high to some extent. High work gas turbines [15][16][17][18] were investigated with the stage pressure ratio higher than 3. The highest outlet Mach number of these turbines was about 1.4.…”
Section: Previous Studies On Transonic Turbinementioning
confidence: 99%
“…Mee et al [10], Michelassi et al [12], Bohn et al [14], Kapteijn et al [47], Vlasic et al [48], Sieverding et al [49], and Tanuma et al [50] investigate losses downstream of transonic airfoils with trailing edge ejection. Mee et al [10], Day et al [45], and Osnaghi et al [51] all indicate that density ratio influences are well correlated using the momentum flux ratio.…”
Section: International Journal Of Rotating Machinerymentioning
confidence: 99%